2018
DOI: 10.32539/sjm.v1i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moringa Leaf Extract (Moringaoleifera) in the Breastfeeding

Abstract: Exclusive breastfeeding for 6 months is a global strategies to promote the growth, development, health and survival of infants. Despite the many benefits of exclusive breastfeeding for infants, mothers, families and communities, the coverage is still low in many countries including Indonesia. Mother's milk is produced from the collaboration between mechanical stimulation of hormonal and nerve factors. One of the hormones that affects is the estrogen. The hormone estrogen is a sex hormone produced by the uterus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
3
0
5
Order By: Relevance
“…The results showed that there was a relationship between the combination of breast care and Moringa leaf steeping water to increase the volume of breast milk. Researchers assume, breast care and the presence of phytosterol compounds in Moringa leaves that function to increase and facilitate breast milk production (Lagtogogum effect) (Septadina et al, 2018). This is in line with the results of research which says that by combining breast care and Moringa leaf steeping water, it will be even better to increase milk production for nursing mothers (Nurul Isnaini, 2015).…”
Section: Discussionmentioning
confidence: 72%
“…The results showed that there was a relationship between the combination of breast care and Moringa leaf steeping water to increase the volume of breast milk. Researchers assume, breast care and the presence of phytosterol compounds in Moringa leaves that function to increase and facilitate breast milk production (Lagtogogum effect) (Septadina et al, 2018). This is in line with the results of research which says that by combining breast care and Moringa leaf steeping water, it will be even better to increase milk production for nursing mothers (Nurul Isnaini, 2015).…”
Section: Discussionmentioning
confidence: 72%
“…Moringa leaves have the ability to improve both the quality and quantity of breast milk. Moringa contains phytosterols, which act as a galactagogue, stimulating breast milk secretion [36][37][38]. Similarly, katuk leaves can boost breast milk production [28,39].…”
Section: Discussionmentioning
confidence: 99%
“…Pengeluaran ASI selama menyusui di pengaruhi oleh asupan nutrisi yang di konsumsi ibu. Terdapat beberapa tanaman yang dipercaya secara turun temurun maupun yang sudah teruji ilmiah kandungannya dalam membantu produksi ASI yaitu daun lembayung (Vigna Sinensis L.), daun katuk (Sauropus androgynus), klabet (Trigonella graceum L.) dan daun bangunbangun (Coleus amboinicus, Lour), kelor (Moringa Oleifera), daun labu kuning (curcubita moshata) (Firdausi & Laelatul Qomar, 2019) (Septadina et al, 2018) (Triananinsi et al, 2020).…”
Section: Kajian Pustakaunclassified